Keeping Children Safe at Home: Parent Perspectives to Firearms Safety Education Delivered by Pediatric Providers. Issue 5 (May 2020) - DeMello, Annalyn S.; Rosenfeld, Eric H.; Whitaker, Brian; Wesson, David E.; Naik-Mathuria, Bindi J.
Abstract : Objectives: The aims of this study were to assess parent acceptance of firearms education delivered by clinical providers, determine whether parents engage in firearms safety dialog with their children, and evaluate reasons for ownership and storage behaviors. Methods: The parents of children ages 0 to 18 years completed surveys while in a pediatric inpatient setting in Texas. Demographics, acceptability, current behaviors, and storage practices were queried. Responses between firearms owners and nonowners were analyzed using the Fisher exact and χ 2 tests. Results: Of the 115 parents who completed surveys, 41% reported owning firearms. Most parents were likely or highly likely to follow their pediatrician's gun safety advice (67%), were accepting of safety videos in waiting rooms (59%), and accepted firearms locks distributed by clinical providers (69%). Nonowners were less likely than owners to have spoken to their children about gun safety ( P = 0.004). Parents owned firearms for self-protection and recreation (50%), self-protection only (38%), or recreation only (12%). Owners stored them unloaded (75%), used safety devices (95%), and stored them in the closet of the master bedroom (54%). Conclusions: Talking about firearms safety in a healthcare setting was not a contentious issue in the majority of our sample. Parents were accepting of provider-led firearms guidance regardless of ownership status. This provides an opportunity for providers to focus on effective messaging and time-efficient delivery of firearms safety education. Abstract : The authors believe that it is well within the scope of hospital institutions to address firearms safety within the homes of our pediatric patients. To tailor effective practices to the needs of the community, they surveyed the parents of children admitted to a surgical unit of our hospital (including for trauma-related injuries). The authors sought to understand whether parents would accept firearms safety education delivered within a pediatric clinic, and ascertained reasons behind firearms ownership and how owners stored their firearms.